2012
DOI: 10.22610/imbr.v4i1.961
|View full text |Cite
|
Sign up to set email alerts
|

Thai Consumers’ Perception on Herbal Cosmetic Products: A Comparative Study of Thai and Imported Products

Abstract: This research investigated the factors that influence perception of Thai consumers on facial herbal cosmetic products in Thailand. In- depth interview the perception of Thai consumers was utilized in data collection, while content analysis was employed in data analysis. The facial herbal cosmetics products are moisturizer, whitening lotions, creams, powder, toner, make up cleansing, mask, cleansing oil, soap bar, anti-aging lotions and creams. This study revealed that most of the interviewees were female with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 8 publications
0
10
1
Order By: Relevance
“…As per Kountur and Huo (2013), medicinal properties, product appearance and distribution explain for 44.81 per cent of variance that makes people attracted towards herbal medicines. Product appearance was also reported by some studies as a determinant of purchase of herbal medicines (Kamboj, 2000; Thanisorn et al, 2012). Affordability or lesser price was reported as a determinant affecting consumers’ perception of brands and their buying decisions (Naresh & Reddy, 2016).…”
Section: Review Of Literaturementioning
confidence: 73%
See 2 more Smart Citations
“…As per Kountur and Huo (2013), medicinal properties, product appearance and distribution explain for 44.81 per cent of variance that makes people attracted towards herbal medicines. Product appearance was also reported by some studies as a determinant of purchase of herbal medicines (Kamboj, 2000; Thanisorn et al, 2012). Affordability or lesser price was reported as a determinant affecting consumers’ perception of brands and their buying decisions (Naresh & Reddy, 2016).…”
Section: Review Of Literaturementioning
confidence: 73%
“…A study by Thanisorn, Byaporn, and Chanchai (2012), amongst Thai customers, found that the marketing mix elements comprising of the 4 Ps, product, place, price and promotion, were the most important influence on consu-mer’s perception of herbal medicine products. Another study by Huda and Sultan (2013) also found that the younger generations were influenced by the marketing mix elements of accessibility, availability, awareness, affordability and PQ while buying herbal products.…”
Section: Review Of Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Consumer perception and buying behaviour towards ayurvedic medicines across India was studied by several researchers in India and there is consensus among the researchers that (a) people are more interested in buying Ayurvedic products compared to the chemical product/medicine (Sharma & Khanna, 2017) and (b) that customers prefer to buy ayurvedic products for relief from stressful working culture, exhaustive lifestyle, the endless quest for peace and growing ailments issues with less healthy environment (Sangeetha, 2017). Some studies performed in other countries (e.g., Thailand, Bangladesh) also emphasised that (a) customers have high trust in herbal products, (b) consumers were influenced by the physical appearance of the herbal products, attractive texture, odour, penetration-characteristic, viscosity, cash discount, gift premium, fortune, tarot horoscope, make-up and massage workshop and (c) women show growing importance to herbal cosmetic products (Chattaraj et al, 2018; Thanisorn et al, 2017). In one study conducted in Siberia, majority of Siberians are well-educated and they consume herbal remedies on their own initiative and manufacturers of herbal drugs in Siberia also educate potential consumers on reliable use of herbal medicines and herbal dietary supplements in order to improve their awareness on extensive use of herbal remedies by overcoming safety and potential risks while using combination with other drugs (Samollk et al, 2013).…”
Section: Ayurveda and Nature-based Herbal Productsmentioning
confidence: 99%
“…In Thailand, some researchers found that Thai consumers buy herbal facial cosmetic products because of attractive texture, odour, penetration characteristic, viscosity, cash discount, gift premium, fortune, tarot horoscope, make-up and massage workshop, etc. (Thanisorn et al, 2017). The study also revealed that Thai consumers are highly influenced by branded products, which are advertised through leaflets, fashion magazines, television and radio shows.…”
Section: Relationship Between Consumer Attitude and Brand Awareness mentioning
confidence: 99%